Hybrid integrators with predictive overload estimation for analog computers and continuous-time ΔΣ modulators - D. Killat; B. Ulmann; S. Köppel (Advances in Radio Science, 2023)
Continuous-time integrators are a central component in ΔΣ modulators, in analog computers, and general analog signal processing. If several integrators are interconnected, scaling plays an important role: In analog computers, scaling is performed with respect to the machine unit (MU). In ΔΣ modulators, scaling is performed in such a way that at maximum input signal the allowable dynamic range of no integrator is exceeded. In both cases the scaling is a compromise limiting the dynamic range.